the Aesthetics Of Artistic Composition In The Poems Of Prophetic Praise By The Algerian Poet Ahmed Sahnoun. - djeridi, Samir (El Omda in Linguistics and Discourse Analysis, 2025)
.The article deals with the aesthetics of artistic composition in the poems of prophetic praise by the Algerian poet Ahmed Sahnoun (1906 AD - 2003 AD); he introduces the poet briefly, then addresses the concept of prophetic praise in general, and highlights the manifestations of praise in the poems in question by referring to them in the poet’s collection. Or quote some of its versesDiscussing the aesthetics of artistic formation in it (meters and rhymes, content, language, and poetic image), All of this in a concise manner that aligns with publishing standards and requirements, so that the article ends with a conclusion summarizing the most important results reached.